Speech Recognition With the Advanced Combination Encoder and Transient Emphasis Spectral Maxima Strategies in Nucleus 24 Recipients. - Holden, Laura K.; Vandali, Andrew E.; Skinner, Margaret W. (Journal of Speech, Language & Hearing Research, 2005)
One of the difficulties faced by cochlear implant (CI) recipients is perception of low-intensity speech cues. A. E. Vandali (2001) has developed the transient emphasis spectral maxima (TESM) strategy to amplify short-duration, low-level sounds. The aim of the present study was to determine whether speech scores would be significantly higher with TESM than with the advanced combination encoder (ACE) strategy fitted using procedures that optimize perception of soft speech and other sounds. Eight adult recipients of the Nucleus 24 CI system participated in this study. No significant differences in scores were seen between ACE and TESM for consonant-vowel nucleus-consonant (CNC) words presented at 55 and 65 dB SPL, for sentences in noise presented at 65 dB SPL at 2 different signal-to-noise ratios, or for closed-set vowels and consonants presented at 60 dB SPL. However, perception of stop consonants within CNC words presented at the lower level (55 dB SPL) was significantly higher with TESM than ACE. In addition, percentage of information transmitted for words at 55 dB SPL was significantly higher with TESM than with ACE for manner and voicing features for consonants in the initial word position. Analysis of closed-set consonants presented at 60 dB SPL revealed percentage of information transmitted for manner was significantly higher with TESM than with ACE. These improvements with TESM were small compared with those reported by Vandali for recipients of the Nucleus 22 CI system. It appears that mapping techniques used to program speech processors and improved processing capabilities of the Nucleus 24 system contributed to soft sounds being understood almost as well with ACE as with TESM. However, half of the participants preferred TESM to ACE for use in everyday life, and all but 1 used TESM in specific listening situations. Clinically, TESM may be useful to ensure the audibility of low-intensity, short-duration acoustic cues that are important for understanding speech, for recipients who are difficult to map, or if insufficient time precludes the use of mapping techniques to increase audibility of soft sound. Reprinted by permission of the publisher.